The mediating role of sexually selected traits in the association of androgynous tendencies with lower sexual activeness among Chinese youths - Zhao, Shuangyu; Guo, Fuyu; Hee, Jia Yi; Tang, Kun (Frontiers in Psychology, 2022)
In recent decades, androgynous tendencies and persistently low fertility rates have been observed in many East Asian and European countries, causing major economic and social concerns. The theory of sexual selection suggests that there is a possible mechanism between androgyny and decreasing sexual activeness since masculinity and femininity constitute one aspect of reproductive strategies; this theory has also been proven by evolutionary and societal evidence. The present study investigates the association between masculinity and femininity with sexual activeness among 42,492 Chinese youths, as well as the influence of gender-role conformity on the frequency of sexual intercourse through sexual selection-related factors. Sexual attitudes, experience, behaviors, and pleasure are used to measure sexual activeness. These associations are analyzed using mediation analysis to investigate the mediating effects of sexual selection-related factors such as physical attractiveness, sexual motivation, and interpersonal relationships. We find that low sexual activeness is associated with low gender-role conformity among Chinese youths. Moreover, our study suggests that physical attractiveness, sexual motivation, and interpersonal relationships may mediate such an association, which supports the males-compete/females-choose (MCFC) model. This study contributes to the literature on sexual selection theory and provides a possible explanation for declining overall fertility in a society due to androgynous tendencies.